Optimum Roller Cone Bit Selection Using Image Processing Techniques and Artificial Intelligence Tools - MOMENI, MOHMMADSADEGH (2018)
Bit selection plays an important role in increasing the rate of penetration (ROP) and decreasing the drilling time for the reduction of drilling cost. Factors such as rotary speed, weight on bit and bit features have a considerable effect on drill bit optimization.